A Study Exploring the SHG-Bank Linkage Programme and Women Empowerment in the Southern Region of India - Navena Nesa Kumari, J.; Veerashekarappa,; Joe Arun, C. (Prabandhan: Indian Journal of Management, 2019)
Microcredit is a great choice for rural women as it provides them the required economic and social skills to face challenging environments. The purpose of the paper was to review the self-help group-bank linkage programme (SBLP) in five southern states of India, namely Andhra Pradesh (undivided), Karnataka, Tamil Nadu, Kerala, and Puducherry for a period of 2012–2017. Commercial banks - public, private, regional rural banks, and cooperative banks - are involved in the linkage programme because of their mandatory disclosure with the SBLP. The self-help groups' (SHGs) loans disbursement in the selected states was found to be high among the cooperative banks. It was observed through the analysis that the cooperative banks played an important role in Karnataka and Tamil Nadu. The private sector banks also played a significant role in the linkage programme, if the state strongly intervenes. The research study led to the inference that though the number of women SHGs was increasing every year, the SHGs managed to save and repay the loans within the stipulated period. It was observed from the study that the savings - bank linkages varied across the states, and the linkages depended on various parameters.